Decreased expression of SCARA5 predicts a poor prognosis in melanoma using bioinformatics analysis - Ni, Qinggan; Li, Xia; Huang, Hua; Ge, Zili (Frontiers in Oncology, 2023)
Background It has been established that the scavenger receptor class A member 5 (SCARA5) functions as a tumor suppressor gene in various cancer types. To our knowledge, no comprehensive study has hitherto investigated the expression and function of SCARA5 in melanoma. This study aimed to determine the association between SCARA5 and melanoma. Methods Analysis of SCARA5 mRNA expression was performed using The Cancer Genome Atlas (TCGA) data sets. To evaluate the clinical significance of SCARA5, the clinical data of 93 patients with melanoma were collected. The role of SCARA5 expression in prognosis was also analyzed. In this study, survival was evaluated by Kaplan–Meier analysis and compared using the log-rank test. Univariate and multivariate Cox proportional hazard regression analyses were used to identify independent predictors. The Kyoto Encyclopedia of Genes and Genomes, Gene Ontology, and gene set enrichment analysis (GSEA) were used to perform gene set functional annotations. Protein–protein interaction (PPI) networks were constructed to illustrate gene–gene interactions. The Tumor IMmune Estimation Resource (TIMER) database was used to explore the association between SCARA5 and immune infiltration levels. Results The results showed that the SCARA5 mRNA expression in melanoma was significantly lower than in adjacent normal skin tissue (p < 0.001). Moreover, decreased expression of SCARA5 in melanoma correlated with the tumor, node, and metastasis (TNM) stage and recurrence (p < 0.05). The overall survival (OS) was significantly higher in melanoma with high SCARA5 expression compared with low SCARA5 expression (p < 0.001). During univariate analysis, SCARA5 expression, tumor (T) stage, node (N) stage, metastasis (M) stage, and recurrence correlated with OS (p < 0.05). Further multivariate Cox regression analysis showed that SCARA5 expression (p = 0.012) could be an independent prognostic factor for OS in cutaneous malignant melanoma. GSEA analysis showed that SCARA5 was significantly enriched in various pathways, such as response to developmental biology and response to antimicrobial peptides. Correlation analysis showed a positive correlation with CD8+ T cells, CD4+ T cells, macrophages, neutrophils, and dendritic cells (p < 0.05), and a negative correlation with tumor purity (p < 0.05) Conclusion SCARA5 has significant potential as a prognostic biomarker and as a promising therapeutic target in melanoma. Furthermore, SCARA5 expression in melanoma is related to the level of immune infiltration.